STAGES OF FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS BY MEANS EXTRACURRICULAR WORK OF HIGHER EDUCATION INSTITUTIONS - Havrylyuk, O.O. (Pedagogy of Higher and Secondary Education, 2022)
The article shows the advantage of stage by stage forming comunicative culture, revels the contents of each stage.